Impacts of Four Decades of Forest Loss on Vertebrate Functional Habitat on Borneo - Ocampo-Peñuela, Natalia; Garcia-Ulloa, John; Kornecki, Itto; Philipson, Christopher D.; Ghazoul, Jaboury (Frontiers in Forests and Global Change, 2020)
Tropical forests are undergoing drastic transformations, putting at risk the species that rely on them. On the island of Borneo, between 1973 and 2015, 50% of the forest has been lost, much of this to oil palm and other industries. We explore the impacts of these four decades of forest loss on the functionally connected habitat of 245 forest birds and mammals. First, we map potential suitable habitat in 1973 and 2015 by refining reported ranges by elevation, forest cover and patch size. We find that, on average, these species have lost 28% of habitat within their ranges. Then we use graph-theory connectivity models to calculate the amount of area that is functionally connected for each species, according to their natal dispersal abilities. This analysis shows a mean loss of 35% of their connected habitat and reveals the larger, and often hidden, impacts from deforestation. Losses in functionally connected habitat are largely driven by area of habitat loss, yet maximum elevational range limit also explain some of the differences modelled across species with lowland species being the most affected. We present a vulnerability index of threat arising from functionally connected habitat loss. The spatial aggregation of this vulnerability index serves as a tool for setting conservation priorities for forest remnants on Borneo, given that most of the ranges of these species are not protected. We make recommendations for the use of connectivity models to prioritize resources for research and conservation on Borneo and other biodiversity hotspots.